Development of a Psychosociolinguistics-Based Role Play Model in Arabic Language Learning - Novian, Zailani; Abdul Munip (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study seeks to investigate the current practices in Arabic language instruction and to formulate a role play-based instructional model grounded in a psychosociolinguistic framework, with the objective of enhancing students speaking proficiency (maharah al-kalam). Employing a qualitative descriptive methodology, data were gathered through classroom observations, in-depth interviews, and document analysis. The participants consisted of Arabic language teachers and junior secondary school students. The findings reveal that instructional activities remain predominantly conventional, characterized by lecture-based delivery and text-centered exercises. Students oral communication skills are notably underdeveloped, primarily due to the absence of communicative and context-driven speaking opportunities. Furthermore, while teachers are generally unfamiliar with the theoretical construct of psychosociolinguistics, they intuitively acknowledge the significance of psychological and social factors in fostering effective language learning. In response to these conditions, a role play instructional model was designed, comprising three integrated stages: preparatory activities (psycholinguistic), role simulation within authentic social contexts (sociolinguistic), and post-activity reflection. This model is deemed pedagogically viable and relevant for broader implementation in Arabic language instruction, particularly in facilitating the development of students speaking competence through interactive, contextualized, and student-centered learning experiences.